Experiences of Establishing Up-To-Date On-Site Sampler Applications - Pázmányi, Sándor; Dobos, Attila (Acta Agraria Debreceniensis, 2005)
Spatial problems and spatial decisions are decisive in agricultural-environmental informatics systems and the solutions require systems that can collect, evaluate and display spatial data. The distinctive features of spatial informatics systems therefore have to be considered when establishing integrated spatial informatics systems. However, the prepared spatial evaluations are not the only „added value” elements of a completed informatics system. The method of access can also speed up the work of participants and the whole system, making it more efficient with simple data-handling and the application of open standards. The significance of prepared database archives can also increase, since the accumulated data-assets are easy to utilize and become marketable.